The Role of Paskibra Extracurriculars in Developing Students' Social Skills - Sofia Siti Ramdani, Sofia Siti Ramdani; Triani Widyanti; Ade Suherman (Institut Pendidikan Indonesia, 2024)
The background of this research is that extracurricular development can be beneficial for schools, namely as a means of promoting schools to the community, especially the community around the school. With the achievements obtained by the school, it will increase the degree of the school in the eyes of the community. The activities held in the extracurricular program are based on the objectives of the school curriculum. The purpose of this study was to identify aspects of social skills that students need to have, namely the skills of living together and working together, being able to place themselves in a social environment, respecting others. The research method used qualitative method with qualitative descriptive type, data collection techniques by observation, interviews and documentation studies. The results of the study show that the implementation strategy in developing students' social skills at SMPN 1 Pasirwangi certainly has several elements of supporting factors, including that the family is the first and foremost place for children to get an education. The psychological satisfaction obtained by children in the family will greatly determine how they will react to the environment. the growth of self-adjustment ability, from the beginning the child is taught to better understand himself (strengths and weaknesses) so that he is able to control himself so that he can react naturally and normatively.